Application of Permaculture Practices to Improve Sustainable Agriculture in the Maltese Islands - Baron, Byron (Journal of Farming, 2023)
Small island states, such as Malta face numerous, unique challenges in relation to agricultural sustainability, with solutions amenable to larger states being unfit given the particular characteristics of the island. These include the poor soil conditions, the limited water resources, the aging farmer population, farming being mainly part-time, and most farmers having no formal training. Currently farmers practice intensive agriculture to achieve higher crop productivity at lower production costs by relying heavily on agri-chemicals and over-extracting groundwater. This destroys the Maltese natural environment and urges for the development and implementation of sustainable agriculture practices, whereby traditional farming is supplemented with sustainable alternatives such that local agriculture remains productive in the long-term while safeguarding the local environment. Here we outline some of the critical issues that urgently need to be addressed and potential ways forward in relation to soil, water and biodiversity, implementing permaculture principles in small-scale, practical actions in order to improve the sustainability of local agricultural through a combination of scientific evidence, agricultural technology and traditional practices.
Keywords: Sustainable agriculture; soil conservation; ecosystem services; permaculture; Maltese islands.Running title